EFISIENSI DALAM PEMBIAYAAN PENDIDIKAN UNTUK MENINGKATKAN KUALITAS PENDIDIKAN - Rahman, Ansar (Pascasarjana Universitas Negeri Makassar, 2017)
The concept of education quality means that all the ability of educational institutions to fulfill all the desires of their customers, in this case students. The main driver in allocating these resources is budgeting, where in budgeting the focus of the problem is determining the level of expenditure to finance various activities to achieve educational goals. In the quality approach, the role of financing seems clearer, because the efficient use of education costs is seen as the placement of every business that must be able to improve the quality of education. Therefore, giving priority to educational input factors can spur student learning achievement, and education quality as the output of the education process. Improving the quality of education is an important thing to pay attention to and it has consequences for the education budget